Analyzing and Selecting a Suitable Media for Online Marketing - TERZIU, Hysni (European Journal of Multidisciplinary Studies, 2017)
During the last years, the letter “E” has increased its importance not only in the world of information and communication technology (ICT), virtual businesses, and internet surfing but also in other sectors. It has become an important component for a considerable number of research fields such as in electronic marketing, electronic business, electronic finances, electronic trade, electronic distance learning, and electronic markets among others. The revolution in ICT has changed not only our lives but also the ways how people do business. Recently, it is noted that an increasing number of touristic operators use internet and other electronic media to achieve their marketing efforts by giving in this way priority to electronic marketing as a new philosophy and phenomena. Online marketing has as an aim to provide value to customers by using information technologies. It offers additions instruments to traditional marketing. Continues changes in online trade have a direct impact not only in instruments but also in the objectives and aims that require new tools and the usage of new strategies in order to be achieved. These factors (tools, objectives, aims and strategies) can be used to distinguish the instruments of online marketing from those of traditional marketing. To achieve this goal, traditional marketers use a variety of marketing variables including: price, advertising, distribution, product to satisfy actual and potential customers. Today, many organizations are spending more time and money to create online presence, creating of websites. In traditional marketing, the customer's role has been very passive, but today we can say that the world wide web uses the hypermedia concept which provides a more active role to the visitor of the web. Hypermedia means a variety of media content that can be accessed through hyperlinks and that can be used to conduct online marketing and to provide competitive advantages to the new economy. Studies suggest that technological advances have created new communication models and marketing channels that cause the greater impacts on marketing practices (e.g. the acceptance of electronic media as a living communication tool). This paper tries to present the concepts of Online Marketing and particular attention is provided to the manner on how to analyze which Kosovar or regional media on the Internet has greater visibility and what needs to be done to get the right attention of potential clients of our business.
Keywords: Marketing; internet; analysis; media; strategy; customers; information; communication.